Integrated electrochromic device and preparation method thereof
By adopting an integrated electrochromic device structure and using UV glue and other materials to cure and prepare under ultraviolet light, the problems of complex processes and the use of volatile solvents in the prior art are solved, and the effects of simplifying the process, improving efficiency and safety are achieved.
Patent Information
- Application Number
- CN202510099764.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-18
AI Technical Summary
The preparation process of existing five-layer structure solid electrochromic devices is complex and requires the use of volatile solvents, which is harmful to people and the environment.
The integrated electrochromic device structure is adopted, including a first transparent conductive layer, a hybrid electrochromic layer and a second transparent conductive layer. The hybrid electrochromic layer is composed of UV glue, a solvent, an electrochromic material and an ionic agent, and is prepared by ultraviolet light curing.
The preparation process of solid-state electrochromic devices is simplified, the use of volatile solvents is avoided, the preparation efficiency and safety is improved, and the response speed and color discoloration performance of the device are improved.
Smart Images

Figure CN119644641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochromic devices, and in particular to an integrated electrochromic device and a preparation method thereof. Background Art
[0002] Electrochromic devices refer to devices made of electrochromic materials, and common types include liquid and solid. Among them, the structure of solid-state electrochromic devices is usually a classic five-layer structure, which includes a transparent conductive layer, an electrochromic layer, an electrolyte layer, an ion storage layer and a transparent conductive layer in sequence, and the five-layer structure is mostly in the form of a film layer. In solid-state electrochromic devices, the film formation process of the electrolyte film layer is very important. Common electrolyte film formation processes include gel heating and cooling method, solvent volatilization method, spray method and printing method. At present, the mainstream electrochromic materials are inorganic metal materials.
[0003] The current five-layer solid-state electrochromic device has a complex process and takes a long time. Volatile solvents are required during the preparation process, which is harmful to humans and the environment. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide an integrated electrochromic device and a preparation method thereof, wherein the synthesis process is simple and no volatile solvent is required.
[0005] To achieve the above object, the present invention provides an integrated electrochromic device, comprising:
[0006] A first transparent conductive layer, a hybrid electrochromic layer, and a second transparent conductive layer;
[0007] The mixed electrochromic layer comprises UV glue, solvent, electrochromic material and ionizing agent.
[0008] Optionally, the mass content of the UV glue in the mixed electrochromic layer is 15% to 75%.
[0009] Optionally, the solvent includes one or more of propylene carbonate, diethylene glycol butyl ether, and N,N-dimethylformamide;
[0010] The mass content of the solvent in the mixed electrochromic layer is 20% to 50%.
[0011] Optionally, the electrochromic material includes one or more of ethyl viologen and ethyl viologen substitutes;
[0012] The ethyl viologen substituent includes one or more of a hexafluoro substituent, a tetrafluoro substituent, and a difluoro substituent of ethyl viologen;
[0013] The mass content of the electrochromic material in the mixed electrochromic layer is 1% to 10%.
[0014] Optionally, the ionic agent includes one or more of lithium hexafluorophosphate, lithium perchlorate, sodium hexafluorophosphate, lithium tetrafluoroborate, and sodium salts corresponding to viologen substitutes;
[0015] The mass content of the ionizing agent in the mixed electrochromic layer is 0.1% to 2%.
[0016] Optionally, the thickness of the first transparent conductive layer is 70nm to 130nm;
[0017] The thickness of the hybrid electrochromic layer is 60 μm-150 μm;
[0018] The thickness of the second transparent conductive layer is 70 nm to 130 nm.
[0019] Optionally, the hybrid electrochromic layer further includes one or more of a nanoscale conductive medium and a coupling agent.
[0020] Optionally, the nanoscale conductive medium includes one or more of nanoscale copper powder, nanoscale graphene, nanoscale carbon powder, and nanoscale ITO powder;
[0021] Optionally, the particle size of the nanoscale conductive medium is 50 to 100 nm;
[0022] Optionally, the mass content of the nanoscale conductive medium is 0.01% to 0.5%;
[0023] Optionally, the coupling agent includes one or more of KH590 silane coupling agent, KH570 silane coupling agent, and KH580 silane coupling agent;
[0024] Optionally, the mass content of the coupling agent is 0.2% to 0.4%.
[0025] The present invention provides a method for preparing the above-mentioned integrated electrochromic device, comprising the following steps:
[0026] The mixed electrochromic material is coated on the surface of the first transparent conductive layer or the second transparent conductive layer, the transparent conductive layer on the other side is covered on the coated surface of the mixed electrochromic material, and the device is cured under ultraviolet light to obtain an integrated electrochromic device.
[0027] Optionally, the curing time is 3 to 8 minutes.
[0028] Optionally, the hybrid electrochromic material is prepared according to the following method:
[0029] mixing a solvent, an electrochromic material and an ionizing agent to dissolve the electrochromic material;
[0030] The mixed material and UV glue are mixed to obtain a mixed electrochromic material.
[0031] Compared with the prior art, the present invention provides an integrated electrochromic device, which comprises in sequence: a first transparent conductive layer, a mixed electrochromic layer, and a second transparent conductive layer; the mixed electrochromic layer comprises UV glue, a solvent, an electrochromic material, and an ionizing agent.
[0032] The integrated electrochromic device provided by the present invention can be prepared by UV curing, which reduces the preparation process requirements of the solid-state electrochromic device. At the same time, the electrochromic material and the electrolyte are mixed in the same glue layer, which can reduce the thickness of the glue layer, making the preparation of the solid-state electrochromic device simple and efficient. There is no volatile solvent in the preparation process, which is harmless to humans and the environment, and is conducive to the industrialization of solid-state electrochromic devices. The test results show that the integrated electrochromic device prepared by the present invention has a fast response speed, excellent color change performance, high transparency, and is friendly to humans and the environment.
[0033] Moreover, currently electrochromic materials generally use polythiophene, polypyrrole, polyacetylene and inorganic polymers. The present invention uses pyridine substitutes as electrochromic materials. Compared with other polymers, the preparation is simpler, the reaction process is mild, and the reaction conditions are simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A schematic diagram of the structure of the integrated electrochromic device provided by the present invention;
[0035] Figure 2 This is an appearance diagram of the integrated electrochromic device prepared in Example 2 of the present invention before power is supplied;
[0036] Figure 3 This is an appearance diagram of the integrated electrochromic device prepared in Example 2 of the present invention after being powered on for 2 seconds;
[0037] Figure 4 This is an appearance diagram of the integrated electrochromic device prepared in Example 3 of the present invention after being powered on for 1.5 seconds;
[0038] Figure 5 This is an appearance diagram of the integrated electrochromic device prepared in Example 4 of the present invention after being powered on for 2 seconds;
[0039] Figure 6 This is an appearance diagram of the integrated electrochromic device prepared in Example 5 of the present invention before power is supplied;
[0040] Figure 7 This is an appearance diagram of the integrated electrochromic device prepared in Example 5 of the present invention after being powered on for 1 second. DETAILED DESCRIPTION
[0041] The present invention provides an integrated electrochromic device, comprising:
[0042] A first transparent conductive layer, a hybrid electrochromic layer, and a second transparent conductive layer;
[0043] The mixed electrochromic layer comprises UV glue, solvent, electrochromic material and ionizing agent.
[0044] The UV glue is an important component in the mixed electrochromic layer. It is a transparent UV glue with the properties of transparency, good adhesion, high light curing efficiency, good ion conductivity and the like.
[0045] The present invention has no particular limitation on the specific type of the UV glue, and it can be a generally applicable transparent UV glue. In some specific embodiments of the present invention, the UV glue is an acrylate UV glue or an allyl UV glue. Preferably, the viscosity of the UV glue is 5000-6000 mpas.
[0046] The mass content of the UV glue in the mixed electrochromic layer is preferably 15% to 75%.
[0047] The solvent is a solvent that can dissolve the UV glue, electrochromic material and ionizing agent, and preferably includes one or more of propylene carbonate, diethylene glycol butyl ether and N,N-dimethylformamide.
[0048] The mass content of the solvent in the mixed electrochromic layer is preferably 20% to 50%.
[0049] The present invention adds UV glue into the electrolyte layer, so that the film forming process of the electrolyte layer becomes simple and efficient.
[0050] The electrochromic material is the main material in the mixed electrochromic layer, and preferably includes one or more of ethyl viologen and ethyl viologen substitutes.
[0051] The ethyl viologen substituent preferably includes one or more of a hexafluoro substituent, a tetrafluoro substituent, and a difluoro substituent of ethyl viologen.
[0052] The mass content of the electrochromic material in the mixed electrochromic layer is preferably 1% to 10%.
[0053] The present invention mixes the electrochromic material and the electrolyte in the same glue layer, so that the manufacturing process of the electrochromic device is simplified and the thickness of the overall device is reduced.
[0054] The ionic agent is a substance that can provide the compensating ions required by the electrochromic material or can improve the ionic conductivity of the color-changing gel layer, and preferably includes one or more of lithium hexafluorophosphate, lithium perchlorate, sodium hexafluorophosphate, lithium tetrafluoroborate, and sodium salts corresponding to viologen substitutes.
[0055] The mass content of the ionizing agent in the mixed electrochromic layer is preferably 0.1% to 2%.
[0056] The mass fraction of the ionizing agent is preferably 0.01% to 1%.
[0057] The total content of the UV glue, the solvent, the electrochromic material and the ionizing agent is 100%.
[0058] The present invention has no special limitation on the materials of the first transparent conductive layer and the second transparent conductive layer, and they may be applicable materials well known to those skilled in the art, preferably single-sided ITO-coated glass.
[0059] The thickness of the first transparent conductive layer is preferably 70 nm to 130 nm.
[0060] The thickness of the mixed electrochromic layer is preferably 60 μm to 150 μm.
[0061] The thickness of the second transparent conductive layer is preferably 70 nm to 130 nm.
[0062] Preferably, in the present invention, the mixed electrochromic layer further comprises one or more of a nano-scale conductive medium and a coupling agent.
[0063] The nanoscale conductive medium preferably includes one or more of nanoscale copper powder, nanoscale graphene, nanoscale carbon powder, and nanoscale ITO powder.
[0064] The particle size of the nanoscale conductive medium is preferably 50 to 100 nm.
[0065] The mass content of the nano-scale conductive medium is preferably 0.01% to 0.5%, more preferably 0.1% to 0.3%, specifically 0.1%, 0.2% or 0.3%.
[0066] The coupling agent is preferably a silane coupling agent.
[0067] The coupling agent preferably includes one or more of KH590 silane coupling agent, KH570 silane coupling agent, and KH580 silane coupling agent.
[0068] The mass content of the coupling agent is preferably 0.2% to 0.4%, more preferably 0.2% to 0.3%.
[0069] The present invention introduces a conductive medium into the mixed electrochromic layer to improve the conductive performance of the device, but the addition of the conductive medium will reduce the transparency of the device. The present invention adopts a nano-scale conductive medium with a particle size of 50 to 100 nm and adds a silane coupling agent to improve the dispersion of the conductive medium, thereby improving the conductive performance of the device without affecting the transparency of the device.
[0070] Preferably, the coupling agent and the conductive medium are dispersed by ultrasound. The temperature of the ultrasonic dispersion is preferably 40-60°C, more preferably 50°C.
[0071] The present invention provides a method for preparing the above-mentioned integrated electrochromic device, comprising the following steps:
[0072] The mixed electrochromic material is coated on the surface of the first transparent conductive layer or the second transparent conductive layer, the transparent conductive layer on the other side is covered on the coated surface of the mixed electrochromic material, and the device is cured under ultraviolet light to obtain an integrated electrochromic device.
[0073] Preferably, the curing time is 3 to 8 minutes.
[0074] The ultraviolet light is preferably provided by a UV lamp.
[0075] Preferably, the hybrid electrochromic material is prepared according to the following method:
[0076] mixing a solvent, an electrochromic material and an ionizing agent to dissolve the electrochromic material;
[0077] The mixed material and UV glue are mixed to obtain a mixed electrochromic material.
[0078] In order to further illustrate the present invention, the following is a detailed description in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.
[0079] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.
[0080] Example 1
[0081] The preparation process of ethyl viologen hexafluoro substituted products is as follows:
[0082] Take 150ml-200ml acetonitrile or dimethylformamide in a 250ml long-necked flask, then add bromoethane and 4,4-bipyridine in a molar ratio of 2:1 to the long-necked flask, and install the condenser reflux and water bath. Stir and react for 20-24 hours at a water bath temperature of 95°C. After the reaction, filter out 1,1-diethyl-4,4-bipyridinium dibromide by vacuum filtration, and dry it at 60°C in vacuum for 2-4h to obtain the intermediate product. Add 1,1-diethyl-4,4-bipyridinium dibromide and ammonium hexafluorophosphate in a molar ratio of 1:1 to 150ml of water for substitution reaction, stir at room temperature for 6h, filter the product with filter paper after stirring, place the product in a vacuum drying oven, and vacuum dry it at 60°C for 4h to obtain ethyl viologen hexafluoro substitution.
[0083] Example 2
[0084] Weigh 2g of propylene carbonate and place it in a 20ml weighing bottle, add 0.04g of ethyl viologen hexafluoro substitution. Ultrasonicate for 5 minutes until the ethyl viologen hexafluoro substitution is completely dissolved, then add 0.01g (mass fraction 0.1%) of ionizing agent lithium hexafluorophosphate and ultrasonicate for 10 minutes until the ionizing agent is completely dissolved to obtain mixed solution A. Mix the above mixed solution A with 2g of acrylate UV glue, and ultrasonicate for 2 minutes until the mixture is uniform to obtain mixed solution B. Mixed solution B is the mixed electrochromic layer material.
[0085] Stick a 3M tape with square holes on the conductive surface of the ITO glass, evenly apply the obtained mixed electrochromic layer material in the 3M adhesive frame, and finally stick the conductive surface of another piece of ITO glass tightly on the 3M adhesive. Among them, the thickness of the ITO glass conductive surface is 70nm~130nm, and the thickness of the mixed electrochromic layer is 140μm. Expose the obtained device to UV light for 3-6 minutes, and finally obtain an integrated electrochromic device. Stick two conductive tapes on the conductive surfaces of the two ITO glasses respectively.
[0086] During the test, two conductive tapes were respectively pasted on the conductive surfaces of the two ITO glass sheets to facilitate the connection of the power supply. A 1.5V DC power supply was used for the power-on test, and a transmittance meter was used for the transmittance test. The results are shown in Table 1.
[0087] Figure 2 and Figure 3 The figures are respectively the appearance pictures of the integrated electrochromic device prepared in this embodiment before and after being powered on.
[0088] Example 3
[0089] Weigh 2g of diethylene glycol butyl ether and place it in a 20ml weighing bottle, add 0.4g of ethyl viologen tetrafluorosubstituted. Ultrasonicate for 5 minutes until the ethyl viologen tetrafluorosubstituted is completely dissolved, then add 0.01g (mass fraction 0.1%) of ionizing agent lithium tetrafluoroborate and ultrasonicate for 10 minutes until the ionizing agent is completely dissolved to obtain mixed solution A. Mix the above mixed solution A with 4g of allyl UV glue, and ultrasonicate for 2 minutes until the mixture is uniform to obtain mixed solution B. Mixed solution B is the mixed electrochromic layer material.
[0090] Stick a 3M tape with square holes on the conductive surface of the ITO glass, evenly apply the obtained mixed electrochromic layer material in the 3M adhesive frame, and finally stick the conductive surface of another piece of ITO glass tightly on the 3M adhesive. Among them, the thickness of the ITO glass conductive surface is 70nm~130nm, and the thickness of the mixed electrochromic layer is 140μm. Expose the obtained device to UV light for 3-6 minutes, and finally obtain an integrated electrochromic device. Stick two conductive tapes on the conductive surfaces of the two ITO glasses respectively.
[0091] During the test, two conductive tapes were respectively pasted on the conductive surfaces of the two ITO glass sheets to facilitate the connection of the power supply. A 1.5V DC power supply was used for the power-on test, and a transmittance meter was used for the transmittance test. The results are shown in Table 1.
[0092] Figure 4 This is the appearance of the integrated electrochromic device prepared in this embodiment after power is supplied.
[0093] Example 4
[0094] Weigh 2g of N,N-dimethylformamide and place it in a 20ml weighing bottle, add 0.2g of ethyl viologen hexafluoro substituted. Ultrasonicate for 5 minutes until the ethyl viologen hexafluoro substituted is completely dissolved, then add 0.01g (mass fraction 0.1%) of the corresponding sodium salt of the ionizing agent viologen substituted and ultrasonicate for 10 minutes until the ionizing agent is completely dissolved to obtain a mixed solution A. Mix the above mixed solution A with 2g of acrylate UV glue, and ultrasonicate for 2 minutes until the mixture is uniform to obtain a mixed solution B. Mixed solution B is the mixed electrochromic layer material.
[0095] Stick a 3M tape with square holes on the conductive surface of the ITO glass, evenly apply the obtained mixed electrochromic layer material in the 3M adhesive frame, and finally stick the conductive surface of another piece of ITO glass tightly on the 3M adhesive. Among them, the thickness of the ITO glass conductive surface is 70nm~130nm, and the thickness of the mixed electrochromic layer is 140μm. Expose the obtained device to UV light for 3-6 minutes, and finally obtain an integrated electrochromic device. Stick two conductive tapes on the conductive surfaces of the two ITO glasses respectively.
[0096] During the test, two conductive tapes were respectively pasted on the conductive surfaces of the two ITO glass sheets to facilitate the connection of the power supply. A 1.5V DC power supply was used for the power-on test, and a transmittance meter was used for the transmittance test. The results are shown in Table 1.
[0097] Figure 5 This is the appearance of the integrated electrochromic device prepared in this embodiment after power is supplied.
[0098] Example 5
[0099] Weigh 2g of propylene carbonate and place it in a 20ml weighing bottle, add 0.04g of ethyl viologen hexafluoro substitution. Ultrasonicate for 5 minutes until the ethyl viologen hexafluoro substitution is completely dissolved, then add 0.01g (mass fraction 0.1%) of ionizing agent lithium hexafluorophosphate and ultrasonicate for 10 minutes until the ionizing agent is completely dissolved. Finally, add 0.01g of ITO nanopowder and 0.01g of KH590 reagent, ultrasonicate at 50℃ for 4h until the nanopowder is evenly dispersed to obtain mixed solution A. Mix the above mixed solution A with 2g of acrylate UV glue, and ultrasonicate for 2 minutes until the mixture is evenly mixed to obtain mixed solution B. Mixed solution B is a mixed electrochromic layer material.
[0100] Stick a 3M tape with square holes on the conductive surface of the ITO glass, evenly apply the obtained mixed electrochromic layer material in the 3M adhesive frame, and finally stick the conductive surface of another piece of ITO glass tightly on the 3M adhesive. Among them, the thickness of the ITO glass conductive surface is 70nm~130nm, and the thickness of the mixed electrochromic layer is 140μm. Expose the obtained device to UV light for 3-6 minutes, and finally obtain an integrated electrochromic device. Stick two conductive tapes on the conductive surfaces of the two ITO glasses respectively.
[0101] During the test, two conductive tapes were respectively pasted on the conductive surfaces of the two ITO glass sheets to facilitate the connection of the power supply. A 1.5V DC power supply was used for the power-on test, and a transmittance meter was used for the transmittance test. The results are shown in Table 1.
[0102] Figure 6 and Figure 7 The figures are respectively the appearance pictures of the integrated electrochromic device prepared in this embodiment before and after being powered on.
[0103] Example 6
[0104] Weigh 2g of propylene carbonate and place it in a 20ml weighing bottle, add 0.04g of ethyl viologen hexafluoro substitution. Ultrasonicate for 5 minutes until the ethyl viologen hexafluoro substitution is completely dissolved, then add 0.01g (mass fraction 0.1%) of ionizing agent lithium hexafluorophosphate and ultrasonicate for 10 minutes until the ionizing agent is completely dissolved. Finally, add 0.012g of ITO nanopowder and 0.012g of KH590 reagent, ultrasonicate at 50℃ for 4h until the nanopowder is evenly dispersed to obtain mixed solution A. Mix the above mixed solution A with 2g of acrylate UV glue, and ultrasonicate for 2 minutes until the mixture is uniform to obtain mixed solution B. Mixed solution B is a mixed electrochromic layer material.
[0105] Stick a 3M tape with square holes on the conductive surface of the ITO glass, evenly apply the obtained mixed electrochromic layer material in the 3M adhesive frame, and finally stick the conductive surface of another piece of ITO glass tightly on the 3M adhesive. Among them, the thickness of the ITO glass conductive surface is 70nm~130nm, and the thickness of the mixed electrochromic layer is 140μm. Expose the obtained device to UV light for 3-6 minutes, and finally obtain an integrated electrochromic device. Stick two conductive tapes on the conductive surfaces of the two ITO glasses respectively.
[0106] During the test, two conductive tapes were respectively pasted on the conductive surfaces of the two ITO glass sheets to facilitate the connection of the power supply. A 1.5V DC power supply was used for the power-on test, and a transmittance meter was used for the transmittance test. The results are shown in Table 1.
[0107] Comparative Example 1
[0108] 4 g of propylene carbonate was weighed and placed in a 20 ml weighing bottle, and 0.08 g of ethyl viologen hexafluoro substituted was added. Ultrasonication was performed for 5 minutes until the ethyl viologen hexafluoro substituted was completely dissolved, and then 0.02 g (mass fraction 0.1%) of ionizing agent lithium hexafluorophosphate was added and ultrasonication was performed for 10 minutes until the ionizing agent was completely dissolved to obtain a mixed solution A as a mixed electrochromic layer material.
[0109] A double-sided tape with a square hole and the same thickness as the 3M tape used in Examples 1-6 (about 140 μm) is attached to the conductive surface of the ITO glass, and the obtained mixed electrochromic layer material is evenly coated in the 3M adhesive frame, and finally the conductive surface of another piece of ITO glass is closely attached to the double-sided tape. Among them, the thickness of the conductive surface of the ITO glass is 70nm to 130nm, and the thickness of the mixed electrochromic layer is 140μm. Let it stand for 3-5 minutes, and finally obtain an integrated electrochromic device. Two conductive tapes are respectively attached to the conductive surfaces of the two ITO glasses.
[0110] During the test, two conductive tapes were respectively pasted on the conductive surfaces of the two ITO glass sheets to facilitate the connection of the power supply. A 1.5V DC power supply was used for the power-on test, and a transmittance meter was used for the transmittance test. The results are shown in Table 1.
[0111] Table 1 Transmittance test results of Examples 2 to 6 and Comparative Example 1
[0112]
[0113] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. An integrated electrochromic device, comprising: A first transparent conductive layer, a hybrid electrochromic layer, and a second transparent conductive layer; The mixed electrochromic layer comprises UV glue, solvent, electrochromic material and ionizing agent.
2. The integrated electrochromic device according to claim 1, characterized in that: The mass content of the UV glue in the mixed electrochromic layer is 15% to 75%.
3. The integrated electrochromic device according to claim 1, characterized in that: The solvent includes one or more of propylene carbonate, diethylene glycol butyl ether, and N,N-dimethylformamide; The mass content of the solvent in the mixed electrochromic layer is 20% to 50%.
4. The integrated electrochromic device according to claim 1, characterized in that: The electrochromic material includes one or more of ethyl viologen and ethyl viologen substitutes; The ethyl viologen substituent includes one or more of a hexafluoro substituent, a tetrafluoro substituent, and a difluoro substituent of ethyl viologen; The mass content of the electrochromic material in the mixed electrochromic layer is 1% to 10%.
5. The integrated electrochromic device according to claim 1, characterized in that: The ionizing agent includes one or more of lithium hexafluorophosphate, lithium perchlorate, sodium hexafluorophosphate, lithium tetrafluoroborate, and sodium salts corresponding to viologen substitutes; The mass content of the ionizing agent in the mixed electrochromic layer is 0.1% to 2%.
6. The integrated electrochromic device according to claim 1, characterized in that: The thickness of the first transparent conductive layer is 70nm to 130nm; The thickness of the mixed electrochromic layer is 60 μm to 150 μm; The thickness of the second transparent conductive layer is 70 nm to 130 nm.
7. The integrated electrochromic device according to claim 1, characterized in that: The hybrid electrochromic layer further comprises one or more of a nanoscale conductive medium and a coupling agent.
8. The integrated electrochromic device according to claim 7, characterized in that: The nanoscale conductive medium includes one or more of nanoscale copper powder, nanoscale graphene, nanoscale carbon powder, and nanoscale ITO powder; The particle size of the nanoscale conductive medium is 50 to 100 nm; The mass content of the nano-scale conductive medium is 0.01% to 0.5%; The coupling agent includes one or more of KH590 silane coupling agent, KH570 silane coupling agent, and KH580 silane coupling agent; The mass content of the coupling agent is 0.2% to 0.4%.
9. The method for preparing the integrated electrochromic device according to any one of claims 1 to 8, comprising the following steps: The mixed electrochromic material is coated on the surface of the first transparent conductive layer or the second transparent conductive layer, the transparent conductive layer on the other side is covered on the coated surface of the mixed electrochromic material, and the device is cured under ultraviolet light to obtain an integrated electrochromic device.
10. The preparation method according to claim 9, characterized in that: The curing time is 3 to 8 minutes.
11. The preparation method according to claim 9, characterized in that: The hybrid electrochromic material is prepared according to the following method: mixing a solvent, an electrochromic material and an ionizing agent to dissolve the electrochromic material; The mixed material and UV glue are mixed to obtain a mixed electrochromic material.
Citation Information
Patent Citations
Integrated electrochromic device and preparation method thereof
CN113741111A
Weather-resistant electrochromic coating and preparation method thereof
CN115558399A
Image display system
CN115639696A
Transparent-black photocuring electrochromic device as well as preparation method and application thereof
CN116909067A
Electrochromic device and preparation and application thereof
CN117471796A